EVALUASI RUANG BANTARAN SUNGAI PASCA PENATAAN KAWASAN PERMUKIMAN KUMUH DI KELAYAN SELATAN KOTA BANJARMASIN PROVINSI KALIMANTAN SELATAN - Faridl, Difo Miftahul; Hadinata, Irwan Yudha; Mentayani, Ira; Mahyudin, Idiannor (EnviroScienteae, 2023)
The handling of slum areas in Banjarmasin City uses more restoration patterns than renewal and resettlement patterns, and is carried out on land locations only, while riverbank slums are more directed towards rejuvenation and relocation patterns. Evaluation of riverbank space after the arrangement of slum areas in Banjarmasin City, South Kalimantan Province needs to be done in order to analyze the planning principles of handling riverbank slum areas after the implementation/arrangement process and see what factors can determine the success of the handling. Data collection techniques were carried out by literature review, field observations/observations, interviews/FGDs, and distributing questionnaires/digital questionnaires (google form). The sample selection technique used was purposive sampling. The data analysis method used is qualitative and quantitative, which combines descriptive research and percentage numbers. The findings were obtained in the form of analysis of planning principles in the form of slum handling indicators, the level of collaboration of basic elements of slum handling stakeholders and the extent of public/open space in the handling area. then this research also produces factors that determine the success of handling in the form of the level of community satisfaction by utilizing well-operational development infrastructure.